Validation and Cleaning Validation of Equipments in Bulk Drug Manufacturing Facility for Terbutaline Sulphate by HPLC - KATHIRESAN, K.; KANNAN, K.; KANNAPPAN, N.; VENKATESAN, P.; SHENOY, K.R.P. (Asian Journal of Chemistry, 2010)
Validation is a requirement that has always made sense from both a regulatory and quality perspective. Cross contamination is one of the major problems faced in manufacture of bulk drugs, as cross contamination in one batch may lead to the contamination of several batches of pharmaceutical dosage forms. Hence, a cross contamination in active pharmaceutical ingredient facility is one of the greatest contamination leads to inferior quality of final products produced and causes considerable loss to the company. Hence, the relevance of the study about analytical method validation deals with the methods of analysis, definition and theory of method validation. Cleaning validation deals with the methods used for cleaning and sampling techniques. Cleaning validation in bulk drug plant and acceptance limits are fixed by using maximum allowable carry over calculation. The result of present study indicates that the method is suitable for successful implementation in the industry.